2023
DOI: 10.1038/s41557-023-01148-7
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic hexazine [N6]4− anion featured in the complex structure of the high-pressure potassium nitrogen compound K9N56

Abstract: Recent high-pressure synthesis of pentazolates and subsequent stabilization of the aromatic [N5 -] anion at atmospheric pressure had an immense impact on nitrogen chemistry. Here, we present the first synthesis of an aromatic hexazine [N6] 4anion realized in high-pressure potassium nitride K9N56 at 46 and 61 GPa. The extremely complex structure of K9N56 was solved based on synchrotron single-crystal X-ray diffraction and corroborated by density functional theory calculations. This result resolves a long-standi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…These systems are in some sense related to the experimentally known N 6 4− . 45 In the latter, two of the antibonding π* levels are occupied, whereas in the former, they are partially occupied. This makes us hopeful about the possible experimental realization of these systems.…”
Section: Resultsmentioning
confidence: 99%
“…These systems are in some sense related to the experimentally known N 6 4− . 45 In the latter, two of the antibonding π* levels are occupied, whereas in the former, they are partially occupied. This makes us hopeful about the possible experimental realization of these systems.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were compressed to pressures of 54 GPa (DAC1), 63 GPa (DAC2), 70 GPa (DAC3) and 86 GPa (DAC4), and heated to a maximum temperature of 2600(200) K, 3400(200) K, 2500(200) K and to an estimate temperature of 3000 K, respectively. The reaction products of molecular nitrogen with the laser absorbers are described elsewhere 28 , 29 . In all samples, molecular nitrogen surrounding the laser absorbers was also heated, albeit likely to a lower temperature, producing multiple tiny ( < 500 nm) high-quality single-crystals on which Raman spectroscopy, powder X-ray diffraction and single-crystal X-ray diffraction (SCXRD) data were collected.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al 25 reported the synthesis of planar N 6 2À hexazine dianions through potassium azide (KN 3 ) under high pressure. Laniel et al 26 conducted a study on the synthesis of the K 9 N 56 compound by laser heating under high pressure and a first principles calculations. The results revealed that the K 9 N 56 compound comprises a complex arrangement of planar aromatic hexazine [N 6 ] 4À and [N 5 ] À rings, along with neutral nitrogen dimers.…”
Section: Introductionmentioning
confidence: 99%